PENGARUH KONSENTRASI DAN LAMA PERENDAMAN ROOTONE F TERHADAP PERTUMBUHAN STEK NILAM (Pogostemon cablin Benth.) - Aboe B. Saidi (Universitas Teuku Umar, 2018)
This research is conducted with the aim of knowing the influence of concentration and duration of Rootone F optimum for the production of seed / patchouli. The research was conducted at Experimental Garden (KP) of Faculty of Agriculture, Teuku Umar University. The experimental design used Randomized Block Design (RAK) 5 x 3 factorial pattern with 3 replications. The factors studied were rootone F concentration factor and length of soaking cuttings. Thus obtained 16 treatment combinations and overall there are 48 units of experimental unit, where each experimental unit consists of 3 plants, so that numbered 144 plants. Planting media used in this study is top soil soil that has been dried anginkan, manure that has been destroyed first, then sifted then sieves mixed evenly with a ratio of 3: 1 ie 3 parts of soil and 1 part manure then inserted in polybag with weight 3 kg polybag-1, with amount of polybag provided is 162 polybag. Type of ZPT used was rootone-F with concentration of 0 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm according to treatment. The type of solvent used is aquades. The dissolution of ZPT Rootone F is done in a bucket Plastic. Keywords: Pogostemon cablin Benth, long immersion, Rootone F, production, quality of seed